Natural Oil Nanoemulsion-Based Gel Vehicle for Enhancing Antifungal Effect of Topical Luliconazole - Kmkm, Ahmed M.; Ghareeb, Mowafaq M. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Luliconazole, a newer class of imidazole anti-fungal agent, is very effective against several species of fungi, especially dermatophytes. It has very low aqueous solubility acting as a barrier for topical delivery and limiting its dermal availability. Objective: This study aimed to formulate luliconazole oil/water nanoemulsion using the aqueous titration method. Methods: The solubility study resulted in selecting peppermint oil, tween 80, and transcutol p as oil phase, surfactant, and cosurfactant respectively, although the pseudo ternary phase diagram constructs nanoemulsion area for picking formulations. Fifteen o/w nanoemulsion formulations were prepared and characterised for droplet size, polydispersity index, pH values, percent transmittance, and luliconazole content. Among formulations, eight preparations were introduced to enhance the viscosity of prepared nanoemulsions by combining 0.5% carbopol 934 as a gelling agent. Results: The selected preparations demonstrated homogeneous nanoemulgels with pH values appropriate for skin application and accepted luliconazole content. Viscosity results manifested Non-newtonian pseudo plastic behavior with a shear-thinning viscosity profile. In vitro release studies revealed a dissimilar release profile (f2˂50) than that of pure luliconazole dispersion. The results revealed that the formula NG-1 with oil: Smix(2:1):water (15:40:43.5) ratio containing 1% drug and 0.5% carbopol 934 was the optimised formula with excellent spreadability. Conclusion: The study concluded that nanoemulsion-based gel is contemplated an encouraging and proceed technique for the topical preparation and upgrade solubility, dissolution rate and permeability of insufficient water-soluble drugs across the skin.